중국 차문화유산지 관광체험과 몰입이 장소애착에 미치는 영향 연구 - 왕려; Wang Li; 강순화; Kang Soon-hwa (국제문화예술, 2024)
연구목적: 본 연구는 중국 차문화유산의 관광경험은 문화유산에 대한 관광객의 특별한 감정을 응축시키며, 이러한 감정은 문화지각, 정신적 의존, 지역 애착이다. 본 연구는 실증분석을 통해 관광경험, 몰입, 장소 애착 변인 간의 영향 관계를 규명하고자 한다. 연구방법: 문헌분석을 통해 구조화된 모형과 가설을 설정하고, 온·오프라인을 통틀어 총 673개의 유효표본을 분석하였다. 연구결과: 관광경험은 몰입에 유의한 영향을 미치는 것으로 나타났으며, 몰입은 매개변수로서 장소 애착에 유의한 영향을 미치는 것으로 나타났다. 그러나 관광 경험은 장소 애착에 직접적인 영향을 미치지 않는 것으로 나타났다. 즉, 관광객이 차문화유산 관광을 경험할 때 몰입을 통해 장소 애착에 영향을 미칠 수 있음을 보여준다. 결론: 본 논문은 차문화유산에 대한 애착도 향상을 위한 실천적 제언을 제공하고, 차문화유산 관광의 질적 발전에 도움을 주며, 나아가 차문화유산 관광의 명성 제고에 이바지한다. 마지막으로, 중국 차문화유산의 전승과 발전을 실현하는 것이다. Purpose: The tourism experience of Chinese tea cultural heritage condenses tourists’ special feelings about cultural heritage, and these emotions are cultural perception, mental dependence, and local attachment. This study aims to investigate the influence relationship between tourism experience, immersion, and place attachment variables through empirical analysis. Methods: Structured models and hypotheses were established through literature analysis, and a total of 673 effective samples were analyzed both online and offline. Result: Tourism experience was found to have a significant effect on immersion, and immersion was found to have a significant effect on place attachment as a parameter. However, it was found that tourism experience did not directly affect place attachment. In other words, it shows that when tourists experience tea cultural heritage tourism, they can influence place attachment through immersion. Conclusion: This paper provides practical suggestions for improving the attachment to tea cultural heritage sites, helps develop the quality of tea cultural heritage tourism, and further contributes to enhancing the reputation of tea cultural heritage tourism. Finally, it is to realize the transmission and development of Chinese tea cultural heritage.